Understanding Perceptions, Attitudes, Myths and beliefs Towards Public Health(/dentistry) amongst Interns and Post Graduate Students in India amidst COVID-19 Pandemic- A Qualitative Approach - Sonal Kale; Sahana Hegde Shetiya; Shivam Kapoor; Surbhi Tripathi; Punith Shetty (Journal of Indian Association of Public Health Dentistry)
Background: Understanding the perspective of students toward a dental subject is essential as it gives an idea on the positive as well as negative aspects of the subject and helps in planning further changes toward the subject. Aim: The aim of the study was to understand and assess the perceptions, attitudes, myths, and beliefs toward PH dentistry (PHD) among dental interns (DIs) and postgraduate students (PGs) in India through a qualitative approach. Materials and Methods: PGs (n = 10) and DIs (n = 10) representing five zones (East, West, Central, North, and South) were selected for the study from the dental colleges of India for focus group discussion (FGDs) conducted between September 2020 and February 2021. Conceptual framework was prepared pertaining to the aim of the study. FGD was organized through a Zoom meeting. Results: PGs and DIs had different perspectives toward the public health and PHD. The specialty being theoretical was the common response given in both the FGDs. Interns preferred other specialties over PHD for future prospects and lucrative pay. The lack of practicality and importance given to the specialty by higher authorities in India were reported by DIs and PGs, respectively. Conclusion: DIs and PGs have a negative attitude, superimposed with discouraging myths and misconceptions related to PHD with a lack of awareness among DIs regarding the future scope of this specialty. A practical approach to teach students to create interest is needed along with involving PHDs in government health programs.